2022
DOI: 10.1186/s13020-022-00688-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the mechanisms underlying the beneficial effect of Luo Tong formula on retinal function in diabetic rats via the “gut microbiota–inflammation–retina” axis

Abstract: Background Diabetic retinopathy (DR) is a common microvascular complication of diabetes. Luo Tong formula (LTF), a classical traditional Chinese medicine (TCM) prescription, consists of four plants that have been widely and effectively used to treat DR. Previous work in our laboratory has confirmed that LTF can effectively ameliorate DR. However, the potential mechanism underlying the therapeutic effect of LTF on DR has not been fully elucidated. To explore the potential mechanism of action thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This finding led researchers to propose the concept of the ‘gut microbiota inflammatory visual network axis’ (Di et al. 2022 ). The association of this axis with chronic inflammatory states has been increasingly demonstrated in the development of DR.…”
Section: Methodsmentioning
confidence: 99%
“…This finding led researchers to propose the concept of the ‘gut microbiota inflammatory visual network axis’ (Di et al. 2022 ). The association of this axis with chronic inflammatory states has been increasingly demonstrated in the development of DR.…”
Section: Methodsmentioning
confidence: 99%
“…Further investigations on the intervention mechanism of Luo Tong formula demonstrated that it could enhance the expression of cellular tight junction proteins and peripheral proteins to protect the blood–retinal barrier and reduce pathological damage. In addition, Luo Tong formula can significantly enrich beneficial bacteria such as Faecali and Corynebacterium and markedly decrease harmful bacteria such as Enterobacteriales and Bacteroides to effectively reduce systemic and local retinal inflammation [23].…”
Section: Guiding Phenomics Research By the Theory Of State‐target Dif...mentioning
confidence: 99%
“…Recently, noise exposure was found to be associated with the imbalance of the host gut microbiota (Berlow et al, 2021;Chi et al, 2021). Chronic noise exposure was found to have promotive roles in the development of Alzheimer's disease (AD) and diabetes through the dysregulation of host gut microbiota (Verhaar et al, 2021;Di et al, 2022;Park and Wu, 2022;Wang et al, 2022). To provide new clues for the prevention and treatment of noise related disorders, it is necessary to investigate the dysregulations of metabolism and host gut microbes and explore their associations.…”
Section: Introductionmentioning
confidence: 99%